Rb-Sr and Sm-Nd dating of olivine-phyric shergottite Yamato 980459: Petrogenesis of depleted shergottites - Shih,Chi-Yu; Nyquist,Laurence E.; Wiesmann,Henry; Reese,Young; Misawa,Keiji (National Institute of Polar Research, 2005)
P(論文) Martian meteorite Yamato (Y) 980459 has undergone terrestrial weathering in Antarctica. The weathering has affected the Sm-Nd isotopic system. Acid-washed pyroxenes, whole rock and quenched glass samples define a Sm-Nd isochron age of 472±47 (±2σ) Ma and a high initial εNd value of +36.9±2.2 (±2σ). Both values are indisguishable from those reported for the other olivine-phyric depleted shergottite DaG 476. The Rb-Sr system of Y980459 shows even more terrestrial disturbance. The same acid-washed samples, which have a narrow Rb/Sr variation of only～10%, do not yield an Rb-Sr isochron. However, the weighted average of nine samples yields a good initial ^(87)Sr/^(86)Sr ratio value of 0.701384±0.000021 (±2σ) at 472Ma. This value is only slightly higher, by 1-2 ε-units, than that estimated from plagioclase data for DaG 476. Calculations for a two-stage model for Sr and Nd isotopic evolution indicate that Y980459 came from a depleted mantle reservoir with ^(147)Sm/^(144)Nd=～0.266 and ^(87)Rb/^(86)Sr=～0.04, similar to the DaG 476 source. A three-stage model calculation suggests that the REE abundances and Nd isotopic systematics of Y980459 could be produced by partial melting of high ^(147)Sm/^(144)Nd garnet-rich residues which were formed after the extraction of LREE-rich, nakhlite-like melts from a postulated garnet-clinopyroxene-olivine source having ^(147)Sm/^(144)Nd=～0.235. departmental bulletin paper